Evaluación del estado nutricional y su relación con la alimentación en niños de 3 – 5 años del Centro Educación Inicial María Angélica Idrovo del Cantón Vinces provincia Los Ríos del periodo mayo – septiembre 2019 - León Velásquez, Paula Ariana (2019)
Introduction: Currently, preschool feeding is manifested by a minimum consumption of fruits and vegetables and by excess consumption of foods of low nutritional value resulting in malnutrition either due to excess or deficit. Objective: To determine the assessment of nutritional status and its relationship with food in children aged 3-5 years of the initial education center María Angélica Idrovo canton Vinces province Los Ríos 2019. Methodology: The study was quantitative, descriptive, cross-sectional, where the sample was 122 preschool boys and girls in the age of 3-5 years of the María Angélica Idrovo Early Education Center, the anthropometric method was used for the assessment of nutritional status and its interpretation it was through the charts of the growth curves of the Ministry of Public Health; The consumption frequency survey was used to know their diet. Results: The results were that 71% of the population studied is in a normal state, 7% are obese, 20% are overweight, while 1% is emaciated. Children who have more than 5 meals a day have an inadequate diet due to excess risk of obesity, between 4-5 meals a day have an adequate diet with a normal state, and less than 5 meals a day an inadequate diet due to deficit presenting risk of malnutrition. Conclusions: When relating the assessment of nutritional status with preschool feeding, a statistically considerable relationship was obtained between the variables studied.